Radiographic study of the problems and failures of endodontic treatment - Akbar, Iftikhar (International Journal of Health Sciences, 2015)
Objectives: The aim of the present study was to determine radiographically the different reasons and problems of endodontic treatment failure. Methods: The periapical radiographs of 100 patients with one hundred teeth (130 root canals) were examined to identify the problems and failures of endodontic treatment. The various reasons of failure that is under filling, poor filling, over filling and presence of procedural errors were recorded for each root filled canal. Chi square test was used to determine statistical significance between different parameters. Results: Under fillings were found in 46.9% of the root canals. The percentage of poor fillings and over fillings were 28.5% and 13% respectively. Separated instruments and strip perforations were present in 4% and 3% of the teeth, while the presence of furcal perforation and coronal leakage was observed in one case each (1%). Endodontic problems and failures were most commonly observed in molars compare to anterior and premolar teeth. Mesiobuccal, mesiolingual and distobuccal root canals were the most frequently canals with endodontic problems and failures. The relationship between mesiobuccal, mesiolingual and distal canals in mandibular molars and mesiobuccal, distobuccal and palatal canals in maxillary molars in terms of endodontic failures were statistically significant by chi square analysis (P â‰¤ 0.05). Conclusion: The most common cause of endodontic treatment failure was under filling followed by poor filling and over filling and first molar was the most frequently involved tooth with endodontic problems and failures. Keywords: Â Endodontic treatment failure, Endodontic errors, Periapical radiograph, Radiographic evaluation Â